2019
DOI: 10.3390/met9030299
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heat-Treatment on Enhancement of Yield Strength and Hardness by Ti-V-Nb Alloying in High-Manganese Austenitic Steel

Abstract: To deal with the problem of poor yield strength and hardness in the initial use of high-manganese austenitic steel, we investigated the alloying design, microstructure, precipitates, mechanical properties, and comprehensive strengthening mechanism of high-manganese austenitic steel through two novel heat-treatment processes, namely continuous heating process (CHP) and segmented heat preservation process (SHPP). In this work, austenitic Fe-0.9C-17Mn-0.8Si-2.0Cr-0.3Ni-0.5Cu-0.7Mo steels alloyed with Ti, V, and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…As shown in Figure 3b, the precipitation temperature of MC carbides is ≈1350 °C in the experimental steel, which is higher than the formation temperature of austenite. Thus, as the higher temperatures accelerate the diffusion of alloying elements and carbon atoms, some large‐sized MC carbides containing multiple alloying elements will be formed in situ during the solidification of steel, such as (Ti, V, Nb)C, (Nb, V)C, and (Ti, Nb)C. [ 4 ] In addition, the microstructure of tested steel is mostly composed of austenite at 1100 °C. Figure 3b shows the engineering stress–strain curves and tensile test data of the casting specimen, as well as the 1050S, 1100S, 1150S, and 1200S test steels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Figure 3b, the precipitation temperature of MC carbides is ≈1350 °C in the experimental steel, which is higher than the formation temperature of austenite. Thus, as the higher temperatures accelerate the diffusion of alloying elements and carbon atoms, some large‐sized MC carbides containing multiple alloying elements will be formed in situ during the solidification of steel, such as (Ti, V, Nb)C, (Nb, V)C, and (Ti, Nb)C. [ 4 ] In addition, the microstructure of tested steel is mostly composed of austenite at 1100 °C. Figure 3b shows the engineering stress–strain curves and tensile test data of the casting specimen, as well as the 1050S, 1100S, 1150S, and 1200S test steels.…”
Section: Resultsmentioning
confidence: 99%
“…Zhou et al reported that a sufficient amount of Gmicrometer/submicrometer precipitated particles was distributed in cast Ti–V–Nb‐alloyed high‐Mn steel, and the micrometer particles were mostly composed of C, and Nb, with a small V and Ti content, whereas the submicrometer precipitates were mostly composed of vanadium carbides. [ 4,5 ] According to Yong, [ 23 ] VC has the largest solubility product in austenite compared with TiC and NbC, thereby TiC and NbC can precipitate during solidification, whereas large amounts of fine VC particles tend to precipitate at lower temperatures. Therefore, we speculated that the decreased average size and density of the precipitates observed in the experimental steels during the solid‐solution treatment processing were mainly related to the solution of VC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the production of medium and thick plates from high-manganese steel for storage tanks, a combination of hot rolling and subsequent heat treatment is commonly employed to control the resulting microstructure and properties (as shown in Figure 1). Upon undergoing hot processing, alloying elements display unique action mechanisms within high-manganese austenitic steels at low temperatures [26,27]. Reproduced with permission from ref.…”
Section: Introductionmentioning
confidence: 99%